Impacts of E-service Quality on Customer Satisfaction: A Case Study of Lazada - Thi Hoai Nhung, Duong; Ngan, Nguyen Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
The most important issue for online shopping providers is how to retain customer satisfaction. To survive and thrive, they must improve their service quality. This study aims at identifying factors that affect Lazada’s customer satisfaction on its e-service quality as a leading e-commerce market in Vietnam. Data was gathered from 220 customers who used Lazada to buy products. The model test indicates four factors that positively influence customer satisfaction in terms of e-service quality at Lazada including web design, security, fulfillment, and customer service. A number of managerial implications are proposed for Lazada and other online shopping providers to improve service quality.